Contribution of tourism to economic development in the BaPhalaborwa area in Limpopo Province - Mathebula, Benjamin Magezi (University of Limpopo (Turfloop Campus), 2013)
Literature has shown that tourism provides benefits such as revenue generation, employment, regional development and economic prosperity to destination communities. The tourism industry is a highly labour intensive industry; hence it is a valuable source of employment. It employs a large number of people and provides a wide range of jobs, which extend from the unskilled to the highly specialised. Tourism industry plays an important role in the Ba-Phalaborwa Municipal economy and it has the potential to address the socio-economic challenges facing the Ba-Phalaborwa municipal area. The study recommends, based on its findings, the importance of tourism development in building the economy of Ba-Phalaborwa. Firstly, the municipality should consider establishing a municipal entity as per the provisions of the Municipal Finance Management Act, which will be responsible for tourism in the area. Secondly, a clear marketing strategy for all special events, including the marula festival, in the area should be developed in consultation with all the stakeholders. Thirdly, the infrastructure, such as streets, electricity and sanitation, in the area should be upgraded to meet the future demand and expansion of the tourism industry.
Thesis (M.Dev.) --University of Limpopo, 2013
Keywords: Tourism; Economic development; 338.479168; Tourism -- South Africa -- Limpopo; Economic development -- South Africa -- Limpopo